(untitled) (Journal of Bio-Science, 2024)
Turmeric, or Curcuma longa, has been used widely in Indian subcontinental cuisine, cosmetics, preservatives, and ceremonial purposes. Turmeric has long been used to cure a variety of conditions, including allergies, indigestion, coughing, and other illnesses. This review attempts to close the knowledge gap about the wider range of medical applications of Curcuma longa, with a special emphasis on the pharmacological characteristics of its main ingredients, curcuminoids and essential oils. Turmeric has shown encouraging therapeutic results in recent trials, most notably in the treatment of rheumatoid arthritis, cancer, diabetes, hyperlipidemia, inflammation, microbiological infections, asthma, snake bites, and Alzheimer’s disease. The review objectively evaluates the data pertaining to these assertions, emphasizing aromatic-turmerone and curcumin as main active ingredients. Through a methodical examination of existing literature, this review highlights the possibility of developing turmeric-based novel drugs for modern medicine, thereby contributing to improved health outcomes and quality of life. J. Bio-Sci. 31(2): 67-85, 2023